En nombre de la seguridad Procesos de segurización en el Gulumapu y la Frontera de Chile 1760-1885 - Contreras Saiz, Mónika (Historamericana, 2022)
The thesis examines the history of the border region in southern Chile between 1760 and 1885 from the perspective of security policy. The focus is on those interactions between the state and indigenous actors involved that can be evaluated as measures to create and guarantee security in this area.